The Balancing acts: Afghanistan, India and strategies for managing Pakistan-Russia engagement in the region - Rasool, Maimoona; Dr. Munawar Hussain; Dr Mariam Asif (Al-Qanṭara, 2024)
The period from 2001 to 2021 saw India establishing robust ties with Afghanistan through significant economic aid and infrastructure development, with a recorded cost of 3 billion, claimed at ensuring Afghan stability. Pakistan, however, viewed these growing India-Afghanistan relations with suspicion, fearing encirclement and increased Indian influence in the region, specifically against its national interests. In response, Pakistan, with support from Russia, engaged with the Taliban to restore their government in Afghanistan by sponsoring peace dialogues with the assistance of China and Iran, thereby seeking to counter US-India collaborative strategies aimed at regional dominance. Hence, within the theoretical frameworks of balance of power, classical neorealism and hegemonic stability theory; this study explores several key aspects of this geopolitical relationship, such as, the impact of Indian investment on the joint interests of Russia and Pakistan, the nature of these joint interests, and whether their policies in Afghanistan can be considered balancing acts against India-US ties. Additionally, it examines potential future policies of Russia and Pakistan in light of expected Indian efforts to reassert influence in the region. By utilizing qualitative analysis of diplomatic communications and policy documents, this study draws on previous literature including works by Shuja Nawaz (2020), Ren Mu (2021) and Kirill Krivosheev (2024) to contextualize the shifting dynamics. As post-15/8/2021 Afghan politics reflect the undermining of India’s strategies for the region, this study also highlights the joint interests of Pakistan and Russia and their balancing acts to ensure that the interim government of the Afghan Taliban aligns with broader regional interests.